2018
DOI: 10.1007/s11250-018-1616-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding slowly fermentable grains on productive variables and amelioration of heat stress in lactating dairy cows in a sub-tropical summer

Abstract: Feeding low-fiber and high-energy diets to dairy cows is one approach to ameliorate heat stress (HS) by reducing heat increment (HI) during digestion. However, rapidly and slowly fermentable cereal grains differ in their HI. The aim of this experiment was to quantify if feeding slowly fermentable grains ameliorated the physiological responses to HS and improved milk production (MP) in dairy cows. Holstein-Friesian lactating dairy cows were housed in shaded pens and were fed either a total mixed ration (TMR) pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…Gantner et al [57] also reported that high-producing Holstein cows had a greater increase in RT than low-producing cows and the Simmental breed was more resistant to HS in terms of changes in daily milk production and somatic cell counts. In line with the findings of the present study, increases in body temperature and RR have also been found to be negatively correlated with overall milk yield [46,58]. Under hot conditions (temperature 24-39 • C and relative humidity 32-60%) a 1 • C increase in ambient temperature can increase respiration rate from 2.8 to 3.3 breaths per minute [59] and all these physiological responses to heat are the cows' coping strategies [19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Gantner et al [57] also reported that high-producing Holstein cows had a greater increase in RT than low-producing cows and the Simmental breed was more resistant to HS in terms of changes in daily milk production and somatic cell counts. In line with the findings of the present study, increases in body temperature and RR have also been found to be negatively correlated with overall milk yield [46,58]. Under hot conditions (temperature 24-39 • C and relative humidity 32-60%) a 1 • C increase in ambient temperature can increase respiration rate from 2.8 to 3.3 breaths per minute [59] and all these physiological responses to heat are the cows' coping strategies [19].…”
Section: Discussionsupporting
confidence: 87%
“…The THI has been found to be weakly to moderately related with core body temperature in lactating dairy cows exposed to HS [34]. Gonzalez-Rivas et al [46] reported of a stronger relationship between rumen temperature and THI than between rectal temperature and THI in cattle maintained in a feedlot. In a review on measurements of peripheral and deep body temperature in cattle, Godyń et al [47] provided a number of references, indicating that the core body temperatures of cattle could be measured via the ear canal, rectum and the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Betaine-supplemented cows also ate more concentrates and spent slightly longer each day ruminating. Elevated temperatures or thermal heat index (THI) during summer are associated with reduced milk production with a lag of between 1 and 3 days [20], and milk production will return to pre-event levels within 5 to 7 days [18]. In the present study, there also appeared to be a similar lag and return to normal production in the control cows, whereas the BET-supplemented cows maintained milk production.…”
Section: Discussionsupporting
confidence: 48%
“…Cows received 15 g of betaine supplementation per day consumed more TMR than that of the control group. Higher environmental temperature and THI decreased the milk production performance of dairy cows with a log of 1 to 3 days after THI [24]. Hall et al [25] stated that the addition of up to 150 g of betaine per day in TMR increases milk production in a linear manner in thermoneutral conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Wdowiak-Wróbel et al [27] reported that betaine supplementation has an osmoprotective effect, and it promotes the growth of favorable microbiota in rumen under environmental stress conditions. It is also noticed that rumen pH fluctuates with betaine supplementation, and this may extend to heat stress conditions, subsequently increasing the temperature of rumen in HS [24]. Peterson et al [28] demonstrated that betaine is metabolized in rumen and converted into acetate, which may play an essential role in fat synthesis.…”
Section: Discussionmentioning
confidence: 99%